The Nitrate-Nitrite-Nitric Oxide Pathway: Findings from 20 Years of the Tehran Lipid and Glucose Study - Bahadoran, Zahra (Int J Endocrinol Metab, 2018)
CONTEXT: We describe here the contributions of the Tehran lipid and glucose study (TLGS) to understanding different aspects of the nitrate (NO(3))-nitrite (NO(2))-nitric oxide (NO) pathway in health and disease. EVIDENCE ACQUISITION: All English-language documents from the TLGS, focused on NO pathway were searched using the PubMed, Scopus, and Embase databases. RESULTS: Reference values of serum concentrations of NO metabolites (nitrate+nitrite or NOx) were 11.5 - 76.4, 10.1 - 65.6, and 10.3 - 66.8 μmol/L in men, women, and the total population, respectively. Circulating NOx was affected by age, smoking habits, menopause status, thyroid hormones, and various pathologic conditions. Elevated serum NOx was related to increased incidence of metabolic syndrome (odds ratio (OR) = 1.75, 95% confidence interval (CI) = 1.19 - 2.59), hypertriglyceridemic-waist phenotype (OR = 1.39, 95% CI = 1.05 - 1.93), chronic kidney disease (OR = 1.86, 95% CI = 1.10 - 3.14) in women, and cardiovascular disease (hazard ratio (HR) = 1.35, 95% CI = 1.01 - 1.80] in the total population. In participants with low vitamin C intake, higher intakes of NO(2) (≥ 8.77 mg/d) were accompanied with increased risk of diabetes (HR = 2.43, 95% CI = 1.45 - 4.05). A decreased risk of hypertension (OR = 0.58, 95% CI = 0.33 - 0.98) and chronic kidney disease (OR = 0.50, 95% CI = 0.24 - 0.89) was observed in response to higher intakes of NO(2). CONCLUSIONS: Circulating NOx is associated with and could predict the risk of metabolic disorders in a general population. Moreover, dietary NO(3)/NO(2) exposure from usual diets seems to contribute to development of noncommunicable diseases.